Antegrade or Retrograde Approach for the Management of Tandem Occlusions in Acute Ischemic Stroke: A Systematic Review and Meta-Analysis - Min, Xiaoli; Du, Jianhua; Bai, Xuesong; Wei, Tao; Dmytriw, Adam A.; Patel, Aman B.; Zhang, Xiao; Xu, Xin; Feng, Yao; Wang, Tao; Wang, Xue; Yang, Kun; et al. (Frontiers in Neurology, 2022)
Background: Acute ischemic stroke (AIS) caused by tandem intracranial and extracranial occlusions is not rare. The optimal strategy between antegrade (extracranial first) or retrograde (intracranial first) approach remains elusive. This systematic review and meta-analysis aims to compare the two approaches. Methods: PubMed, Ovid, Web of Science, and the Cochrane Library were searched for literature comparing the antegrade and retrograde approach for AIS patients with tandem occlusions. Outcomes including successful reperfusion (TICI 2b-3) and 90-day favorable outcome (mRS 0-2), any intracerebral hemorrhage, symptomatic intracerebral hemorrhage, procedural complications, and mortality were evaluated. Risk of bias was assessed using the Newcastle–Ottawa Scale and illustrated by Funnel plot. Heterogeneity was assessed by I2 statistic. Subgroup and sensitivity analyses were also performed. Results: A total of 11 studies comprising 1,517 patients were included. 831 (55%) patients were treated with an antegrade approach and 686 (45%) with a retrograde approach. A higher successful reperfusion rate was achieved in the retrograde group than the antegrade group (83.8% vs 78.0%, OR:0.63,95%CI:0.40-0.99, P=0.04). 90-day favorable outcome (mRS 0-2 at 90 days) was also significantly higher in the retrograde group than the antegrade group (47.3% vs 40.2%; OR: 0.72, 95%CI:0.58-0.89, P=0.002). The incidence of any intracranial hemorrhage (ICH), symptomatic intracranial hemorrhage, 90-day mortality and other complications did not differ between two groups. Conclusions: In AIS with tandem occlusions, a retrograde approach might achieve higher successful reperfusion rates and better functional outcome with comparable safety profile when compared with an antegrade approach. Further prospective controlled studies are needed to confirm this.